PENGARUH LINGKUNGAN KERJA, STRUKTUR ORGANISASI, KEPEMIMPINAN ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP STRES KERJA BAGIAN KEUANGAN PEMERINTAH (Studi Empiris pada Pegawai Bagian Keuangan di Lingkungan Pemerintah Daerah Kabupaten Indragiri Hulu) - Lucy Ayuna Putri; Azwir Nasir; Rofika ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine and obtain empirical evidence whether the work environment, organizational structure, organizational leadership and organizational commitment affect the level of stress. The population in this study were all employees of the finance department of local government Indragiri Hulu district, amounting to 75 people. Selection of the samples in this study using a non-probability sampling method with the type of purposive sampling method sampling technique with certain considerations. Purposive sampling method in this study carried out later restricted to samples that have certain criteria in order to obtain a sample of 63 people. The analysis of data using multiple regression. From the research, we concluded that the work environment, organizational structure, organizational leadership and organizational commitment significantly positive effect on job stress. Further views seen from the determination of test where Adj. R2 of 0.709 or 70.9% indicate that working environment, organizational structure, organizational leadership and organizational commitment affect employee stress. While the remaining 29.1% is influenced by other variables.Keywords: Work Environment, Organizational Structure, Organizational Leadership, Organizational Commitment and Job Stress.